Glucosamine/β-Alanine Carbon Dots Use as DNA Carriers Into E. coli Cells - Devkota, Asmita; Pandey, Anju; Yadegari, Zeinab; Dumenyo, Korsi; Taheri, Ali (Frontiers in Nanotechnology, 2021)
Introducing foreign DNA into bacterial cells is essential in functional genomics and molecular research. Currently, heat shock and electroporation are the two major techniques of gene delivery in bacterial cells. However, both the techniques are time and resource consuming and are limited to a few species or strains of bacteria and there is a need to develop new transformation alternatives. Carbon dots with unique features such as facile synthesis, ease of functionalization, nontoxicity, and biocompatibility are considered novel biomolecule nanocarriers. In this study, we synthesized and evaluated DNA delivery potential of four carbon dots including: 1) amine-coated carbon dots (NH2-FCDs); 2) carboxylate carbon dots (COOH-FCDs); 3) L-arginine and glucose carbon dots (N-CDs), and 4) citric acid and polyethyleneimine (PEI) carbon dots into Escherichia. coli cells. We evaluated the minimum incubation time required for the plasmid DNA delivery and the maximum plasmid size that can be delivered into E. coli cells using these CDs. Bacteria were incubated with carbon dots solution for different lengths of time and plated on selection media. Transformed colonies were counted and data were analyzed to identify the optimum incubation time and measure DNA delivery of these CDs with plasmids of different sizes. Our study demonstrated that among all these CDs, only carboxylate carbon dots (COOH-FCDs) prepared from glucosamine and β-alanine were able to deliver plasmid DNA into E. coli cells and the best incubation time was between 30 and 60 min. The maximum plasmid size that could be delivered using these CDs was approximately 10 kb and transformation efficiency decreased with larger plasmids. This study shows the capacity of COOH-CDs to deliver plasmid DNA into bacteria with an immense potential to combine with modern genome-editing tools. However, further studies are needed to evaluate their potential in DNA delivery in other bacterial strains.